Calidad del servicio al cliente en la Empresa Cicles Sport - Pazmiño Caisa, Miguel Ángel (2022)
In the following investigation, the case study was carried out: the quality of customer service in the Cicles Sport company of the La Maná canton; a good quality of customer service is important for the activities of the company to be carried out effectively, for this reason it began by analyzing the critical points of the quality of customer service that is implemented in cycles sport, starting by knowing the theories or more relevant concepts of how to generate an optimal quality of customer service through websites, articles, books, later an interview was conducted with the owner of Cicles Sport to identify the critical points of the quality of customer service through open questions and keys to understand the operation of said process, finally a survey was applied to the clients of sport cycles because they are the main actors regarding the subject of this investigation, the result of this investigation showed that the company has good quality in the products, imports recognized brands and has a large stock, a variety of spare parts, accessories, but it was evident that According to the surveys carried out on the clients, shortcomings in the attention provided by the collaborators since they stated that often the attention is slow due to the fact that the employees are not trained to provide an adequate quality of service to the client, they also pointed out that it is considered the implementation of a claims mailbox to take into account the needs of customers.